Quantifying the postural demands of patrol officers: a field study. Issue 2 (3rd April 2017) - Cardoso, Michelle; Girouard, Michelle; McKinnon, Colin; Callaghan, Jack P.; Albert, Wayne J.
Abstract : Police officers are at high risk for developing musculoskeletal injuries. This study aimed to determine differences in physical demands of patrol officers during day shifts and night shifts. Sixteen participants were recruited (10 males, 6 females) for in-vehicle observation over one full day shift and one full night shift. Dynamic pressure distribution when seated in the vehicle was assessed and compared between the first and last parts of each shift. Activity characterization and postural analyses were conducted from video that was recorded continuously for the duration of each shift to determine time spent in each task and corresponding postures. Postural analysis and cumulative joint loads were used to identify higher-risk tasks. Several activities caused the officers to adopt non-neutral postures of the neck, shoulders and back. Future work needs to focus on modifying the interior of the vehicle, as well as decreasing exposure time to activities resulting in non-neutral postures.